Transtorno cognitivo leve e atividade física em idosos residentes no município de Uberaba, MG. - PAULO, Thaís Reis Silva de (2012)
The present study aimed to identify: a) the prevalence of physical inactivity; b) the relationship between physical activity and cognitive functions; c) the predictive power of time in practices of physical activities for mild cognitive impairment; d) the prevalence of mild cognitive disorders and e) the relationship of mild cognitive disorders with socio demographic variables of health and habitual physical activity. It was a cross-sectional observational and analytical type study, using exploratory surveys methods and physical performance testing. The population of this study involved 10,683 people, of both sexes, aged >60 years, living in the urban agglomeration of the city of Uberaba, MG. The sample, stratified at random, consisted of 622 subjects, enrolled in one of the 35 Family Health Teams (FHT) in the city. Data collection was performed by a questionnaire in individual interviews dealing with socio demographic information, physical and mental health, anthropometric measurements, functional capacity and habitual physical activity. The level of habitual physical activity in the fields household, leisure, work and transport was evaluated using the International Physical Activity Questionnaire (IPAQ), the long version and adapted for elderly. The mild cognitive impairment and cognitive functions (orientation, attention and calculation, recall and language) were inferred by the Mini Mental State Examination (MMSE). For the data analysis, procedures involved descriptive statistics (mean and standard deviation) and inferential statistics (U test of Mann- Whitney, Chi-square, ROC curve and Poisson s logistic regression models), p<0,05. The prevalence of physical inactivity (<150 minutes/week) was 35,7%, women 32,4%, and men 41,7%. As for the mild cognitive disorders, the prevalence was 16,7%, men 14,7%, and women 17,8%. Physical inactivity was associated with the cognitive functions of orientation and language. The mild cognitive impairment was associated with older age group (≥80 anos), intermediate level of schooling, lower values in the scores of handgrip and physical inactivity. Physical activity of moderate intensity or vigorous, accumulated in various fields during the time >200 minutes/week, in the field household (>150 minutes/week), in transport (>45 minutes/week) and in the sitting time (581 to 640 minutes/day) for women, and the total time spent on practices of activities (>50 minutes/week), on the field of transport (>40 minutes/week) and on the sitting time (625 to 655 minutes/day) for men presented themselves the best cutoff points for predicting the absence of mild cognitive disorders. The findings of this study add relevant evidence of the relationship between mild cognitive impairment and habitual physical activity to the body of knowledge available. Furthermore, they provide information to contribute to formulating more effective interventional strategies aimed at maintaining the mental health of the elderly and strengthen the important role of Physical Education professionals in the actions to promote health.